Dynamics of early rehabilitation care for children with autism spectrum disorder using the DIR/Floortime approach at St. Luke’s Center for Health and Development - N. V. Romanovskiy (Русский журнал детской неврологии)
This article analyzes the dynamics of early comprehensive psychological and pedagogical care for children aged 3 years with autism spectrum disorders (ASD) using the DIR/Floortime approach. The experimental group included 18 ASD patients aged 3 years who attended a special program in Svt. Luka’s Center for Health and Development (Moscow) on a regular basis (2–3 times a week). The comprehensive program included weekly individual classes of 4 types: Floortime therapy, kinesotherapy with elements of sensory integration, game speech therapist-defectologist, and sensory-gaming group. The control group included 19 ASD patients aged 3 years who did not attend special classes. We used the Vineland Adaptive Behavior Scale (VABS) and Functional Emotional Assessment Scale (FEAS) for examination. Children were examined at baseline and after 3 months. We found that children from the experimental group had a significant positive dynamics in their communication skills, daily living skills, motor development, desire for emotional contact, communicative initiative, and two-way interaction. Children from the control group did not demonstrate any significant dynamics of these parameters.